Field Measurement and Evaluation of the Passive and Active Solar Heating Systems for Residential Building Based on the Qinghai-Tibetan Plateau Case - Zhijian Liu; Di Wu; Miao Jiang; Hancheng Yu; Wensheng Ma (Energies, 2017)
Passive and active solar heating systems have drawn much attention and are widely used in residence buildings in the Qinghai-Tibetan plateau due to its high radiation intensity. In fact, there is still lack of quantitative evaluation of the passive and active heating effect, especially for residential building in the Qinghai-Tibetan plateau areas. In this study, three kinds of heating strategies, including reference condition, passive solar heating condition and active solar heating condition, were tested in one demonstration residential building. The hourly air temperatures of each room under different conditions were obtained and analyzed. The results show the indoor air temperature in the living room and bedrooms (core zones) was much higher than that of other rooms under both passive and active solar heating conditions. In addition, the heating effect with different strategies for core zones of the building was evaluated by the ratio of indoor and outdoor degree hour, which indicates that solar heating could effectively reduce the traditional energy consumption and improve the indoor thermal environment. The passive solar heating could undertake 49.8% degree hours for heating under an evaluation criterion of 14 °C and the active solar heating could undertake 75% degree hours for heating under evaluation criterion of 18 °C, which indicated that solar heating could effectively reduce the traditional energy consumption and improve the indoor thermal environment in this area. These findings could provide reference for the design and application of solar heating in similar climate areas.